The Impact of Political Decisions, IFRS Convergence and Political Connections on Real Earnings Management: The Moderating Role of Audit Quality - Whilis Aziz Panji Pamungkas; Lismawati Hasibuan; Yopy Ratna Dewanti; Napiajo; Riani Tanjung (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to investigate the effect of International Financial Reporting Standards (IFRS) convergence and political connections on Real Earnings Management, with audit quality as a moderating variable. The phenomenon of real earnings management is a serious concern because it is difficult for regulators to detect compared to accrual earnings management. Using agency theory as a theoretical basis, this study analyzes how global accounting standards and a company's political proximity influence managerial decisions in manipulating operational activities. The results of the literature synthesis indicate that although IFRS convergence aims to increase transparency, the presence of political connections often creates protection for managers to engage in opportunism. Audit quality, proxied by reputable external auditors (Big Four), is expected to mitigate such behavior. This study contributes to regulators in evaluating the effectiveness of accounting standards and supervision of companies with close ties to political power.